Nausea and vomiting in pregnancy: associations with maternal gestational diet and lifestyle factors in the Norwegian Mother and Child Cohort Study. Issue 13 (7th August 2013) - Chortatos, A; Haugen, M; Iversen, PO; Vikanes, Å; Magnus, P; Veierød, MB
Abstract : Objective: To investigate primarily the dietary intake, as well as demographics and selected lifestyle factors, of women experiencing nausea and vomiting in pregnancy, nausea only, or women who are symptom free. Design: Prospective cohort study. Setting: The Norwegian Mother and Child Cohort Study, a population‐based pregnancy cohort. Sample: Analyses were based on 51 675 Norwegian pregnancies. Methods: Dietary intake was assessed by a self‐reported food frequency questionnaire answered in the first trimester of pregnancy, as were data regarding nausea and vomiting. Chi‐squared tests, one‐way analysis of variance, and multiple linear regression were used. Main outcome measures: Nausea and vomiting in pregnancy (NVP), gestational weight gain (GWG), and dietary intake. Results: We found that 17 070 (33%) women experienced NVP, 20 371 (39%) experienced only nausea, and 14 234 (28%) were symptom free. Women with NVP were younger and heavier at pregnancy onset, with the lowest GWG and highest energy intake during pregnancy, primarily from carbohydrates and added sugars, compared with the other groups ( P  < 0.001). In multiple linear regression analysis of GWG and group adjusted for body mass index (BMI), gestational length, smoking during pregnancy, and energy intake, a significant interaction was found between BMI and group ( P  < 0.001). A significant effect of group ( P  < 0.001) was found in all BMI strata, except among underweight women ( P  = 0.65). Conclusions: Our study suggests that women with NVP are characterised by high intakes of carbohydrates and added sugar, primarily from sugar‐containing soft drinks. Whether higher intakes of carbohydrates are a response aimed to alleviate symptoms, or are actually provoking the condition, is not known.